Importance of AT1 and AT2 receptors in the nucleus of the solitary tract in cardiovascular responses induced by a high-fat diet - Speretta, Guilherme F. [UNESP]; Ruchaya, Prashant J. [UNESP]; Delbin, Maria A.; Melo, Mariana R. [UNESP]; Li, Hongwei; Menani, José V. [UNESP]; Sumners, Colin; Colombari, Eduardo [UNESP]; Bassi, Mirian [UNESP]; Colombari, Débora S. A. [UNESP] (Springer Nature, 2019)
A high-fat diet (HFD) induces an increase in arterial pressure and a decrease in baroreflex function, which may be associated with increased expression of angiotensin type 1 receptor (AT1R) and pro-inflammatory cytokine genes and reduced expression of the angiotensin type 2 receptor (AT2R) gene within the nucleus of the solitary tract (NTS), a key area of the brainstem involved in cardiovascular control. Thus, in the present study, we evaluated the changes in arterial pressure and gene expression of components of the renin–angiotensin system (RAS) and neuroinflammatory markers in the NTS of rats fed a HFD and treated with either an AT1R blocker or with virus-mediated AT2R overexpression in the NTS. Male Holtzman rats (300–320 g) were fed either a standard rat chow diet (SD) or HFD for 6 weeks before commencing the tests. AT1R blockade in the NTS of HFD-fed rats attenuated the increase in arterial pressure and the impairment of reflex bradycardia, whereas AT2R overexpression in the NTS only improved the baroreflex function. The HFD also increased the hypertensive and decreased the protective axis of the RAS and was associated with neuroinflammation within the NTS. The expression of angiotensin-converting enzyme and neuroinflammatory components, but not AT1R, in the NTS was reduced by AT2R overexpression in this site. Based on these data, AT1R and AT2R in the NTS are differentially involved in the cardiovascular changes induced by a HFD. Chronic inflammation and changes in the RAS in the NTS may also account for the cardiovascular responses observed in HFD-fed rats.
Keywords: Baroreflex; Brainstem; Cytokines; Obesity; Renin–angiotensin system